Characteristics of Acute Kidney Injury in the Intensive Care Unit of Dr. Soetomo General Hospital, Surabaya - Putu Laksmi Febriyani; Bambang Pujo Semedi; Widodo Widodo (Humanistic Network for Science and Technology (HNST), 2021)
Acute Kidney Injury (AKI) is one of the causes of morbidity and mortality among people in both developing and developed countries in the intensive care unit (ICU). In Indonesia, the incidence rate is 0.2% while for the Surabaya, AKI research has not been widely carried out and published. This study aims to determine the characteristics of AKI patients in ICU of Dr. Soetomo hospital covers the data distribution of sociodemographic, risk factors, and mortality. This descriptive study involving 23 inpatients at the ICU with AKI as the sample. Samples were selected using total sampling method. Data were collected from medical records with data collection sheets. The results were then analyzed descriptively and tested bivariate using logistic regression. The results showed that 82.6% of the patients were male with the highest age range of 50-56 years old (30.43%). AKI mortality rate in the intensive care unit was 30.43%. The primary diagnosis was diabetes mellitus (34.78%) and the highest exposure factor was a septic shock (38.70%). Factors associated with AKI mortality were diabetes mellitus (p = 0.000) and exposure to septic shock (p = 0.005). Keywords: acute kidney injury; intensive care unit